Do men deserve more credit? A study on gender and caregiving - Preimesberger, Colleen; Midthun, Kayla (My University, 2006)
Care for the elderly population in the United States is fast becoming an issue many families are facing. This study investigated the relationship between gender and willingness of college students to care for aging parents by surveying 24 male and female undergraduate and graduate students at the University of Wisconsin-Stout. It was hypothesized that female college students would be more willing than men to care for aging parents in the assistance categories of personal hygiene and housework. Survey data was statistically analyzed using cross-tabulations, and mean comparisons. Results indicated that males are more willing to provide care in the categories of personal hygiene and housework. These findings did not support the hypothesis of females being more willing to provide care; the implications are that the traditional roles and stereotypes need to be reassessed.
Keywords: Aging parents--Family relationships--Wisconsin--Menomonie; Adult children of aging parents--Wisconsin--Menomonie--Attitudes; Aging parents--Care--Wisconsin--Menomonie; Caregivers--Wisconsin--Menomonie